2016
DOI: 10.1016/j.rasd.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

“You’re telling me!” The prevalence and predictors of pronoun reversals in children with autism spectrum disorders and typical development

Abstract: Social and linguistic explanations have been proposed for pronoun reversals in young typically developing (TD) children and those with autism spectrum disorders (ASD). The current study breaks new ground in investigating both explanations, comparing 18 TD toddlers and 15 children with ASD at similar language levels. Spontaneous speech was sampled every four months for six visits. Vocabulary and joint attention were also measured. Both groups produced pronoun reversals at low rates. The ASD group produced somew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 47 publications
7
80
1
Order By: Relevance
“…In contrast, a new wave of recent research investigating the acquisition of lexical semantics and grammar in children with ASD has revealed a number of findings that are inconsistent with this view . For example, the tendency of children with ASD to reverse personal pronouns—producing ‘I’ when the context calls for ‘you’ and vice versa—has primarily been attributed to these children's lack of interest in and/or sophistication with reciprocal relationships with others; however, we and our colleagues have recently demonstrated that the children's language level, as indexed by their vocabulary size, plays an independent and stronger role in predicting pronoun reversals than their social perspective‐taking, as indexed by their initiations of joint attention …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a new wave of recent research investigating the acquisition of lexical semantics and grammar in children with ASD has revealed a number of findings that are inconsistent with this view . For example, the tendency of children with ASD to reverse personal pronouns—producing ‘I’ when the context calls for ‘you’ and vice versa—has primarily been attributed to these children's lack of interest in and/or sophistication with reciprocal relationships with others; however, we and our colleagues have recently demonstrated that the children's language level, as indexed by their vocabulary size, plays an independent and stronger role in predicting pronoun reversals than their social perspective‐taking, as indexed by their initiations of joint attention …”
Section: Introductionmentioning
confidence: 99%
“…In other analyses of this dataset, we have reported that these children did produce pronoun reversals, albeit at fairly low rates (i.e., averaging no more than 7% of all 1 st and 2 nd person singular pronoun uses; Naigles et al, 2016). For the current study, we revisited the transcripts to ascertain whether any child only produced pronoun reversals (or other pronoun errors) at a given visit.…”
Section: Discussionmentioning
confidence: 59%
“…For the current study, we revisited the transcripts to ascertain whether any child only produced pronoun reversals (or other pronoun errors) at a given visit. However, we found that every child who produced pronoun reversals or other pronoun errors at a given visit also produced as many if not more instances of correct pronoun usage (for more details about pronoun usage in this dataset, see Naigles et al, 2016; Kelty-Stephen, Tek, Fein & Naigles, 2014). Thus, these children should have been given a ‘1’ for those visits; however, many were given a ‘0’, presumably because parents were focusing on the noticeable errors, rather than the many correct uses.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This could indicate that pronoun reversals occur when children's social abilities lag behind their linguistic abilities and derive from social immaturity (cf. Naigles et al, 2016).…”
Section: Discussionmentioning
confidence: 99%